Highly selective copper nanoparticles for the hydrogenation of,-unsaturated aldehydes in liquid phase - Gutierrez, Victoria Soledad (2013)
Unsupported copper nanoparticles (CuNPs), 3–4 nm in size, are obtained from the reduction of the corresponding metal chloride through an electron transfer from a lithium arenide. CuNPs are tested for the liquid phase hydrogenation of cinnamaldehyde in batch conditions by using H2. High activity and selectivity to cinnamyl alcohol (87%, at high conversion) are reached. When CuNPs are supported on MCM-41 and on high surface area CeO2, TEM and XRD characterization shows that the nanometric size of copper is retained. For the hydrogenation of crotonaldehyde or of cinnamaldehyde, CuNPs/MCM-41 and CuNPs/CeO2 are less active and less selective than unsupported nanoparticles. However the selectivity levels reached by these catalysts are higher than those obtained over noble metal (Au and Pt) based catalysts, tested under the same reaction conditions. The catalytic properties of supported and unsupported CuNPs would be related to the nanometric size of copper